Unraveling the nexus of age, epilepsy, and mitochondria: exploring the dynamics of cellular energy and excitability - Xie, Wen; Koppula, Sushruta; Kale, Mayur B.; Ali, Lashin S.; Wankhede, Nitu L.; Umare, Mohit D.; Upaganlawar, Aman B.; Abdeen, Ahmed; Ebrahim, Elturabi E.; El-Sherbiny, Mohamed; Behl, Tapan; Shen, Bairong; et al. (Frontiers in Pharmacology, 2024)
Epilepsy, a complex neurological condition marked by recurring seizures, is increasingly recognized for its intricate relationship with mitochondria, the cellular powerhouses responsible for energy production and calcium regulation. This review offers an in-depth examination of the interplay between epilepsy, mitochondrial function, and aging. Many factors might account for the correlation between epilepsy and aging. Mitochondria, integral to cellular energy dynamics and neuronal excitability, perform a critical role in the pathophysiology of epilepsy. The mechanisms linking epilepsy and mitochondria are multifaceted, involving mitochondrial dysfunction, reactive oxygen species (ROS), and mitochondrial dynamics. Mitochondrial dysfunction can trigger seizures by compromising ATP production, increasing glutamate release, and altering ion channel function. ROS, natural byproducts of mitochondrial respiration, contribute to oxidative stress and neuroinflammation, critical factors in epileptogenesis. Mitochondrial dynamics govern fusion and fission processes, influence seizure threshold and calcium buffering, and impact seizure propagation. Energy demands during seizures highlight the critical role of mitochondrial ATP generation in maintaining neuronal membrane potential. Mitochondrial calcium handling dynamically modulates neuronal excitability, affecting synaptic transmission and action potential generation. Dysregulated mitochondrial calcium handling is a hallmark of epilepsy, contributing to excitotoxicity. Epigenetic modifications in epilepsy influence mitochondrial function through histone modifications, DNA methylation, and non-coding RNA expression. Potential therapeutic avenues targeting mitochondria in epilepsy include mitochondria-targeted antioxidants, ketogenic diets, and metabolic therapies. The review concludes by outlining future directions in epilepsy research, emphasizing integrative approaches, advancements in mitochondrial research, and ethical considerations. Mitochondria emerge as central players in the complex narrative of epilepsy, offering profound insights and therapeutic potential for this challenging neurological disorder.